RESEARCH AREAS IN THE DEVELOPMENT OF EDUCATIONAL MANAGEMENT - Somantri, Manap (Universitas Ahmad Dahlan, 2020)
The objectives of this study are elaboration research areas in the development of educational management at the teacher and educational science faculty. Elaboration of research areas significant for the development of competitiveness study program, and can be references candidates for the topic choices of thesis and dissertation or lecturer research at the teacher and educational science faculty. The study will be done to literature analysis on educational management as a dimension process and substances in education. As a dimension, process management has explored while on planning, organizing, staffing, directing, budgeting, controlling, evaluating, and reporting. Substantial management included the curriculum, student, teacher, staff, money, facilities, and participation in educational management. The organization level can be analyses on global, regional, local, and institutional levels. The organizational function can be analyses on leadership, planning, supervision, communication, decision making, and innovation in the management process. The area's research in educational management has used for institutional innovation and student achievement.